Imaging the distribution of skin lipids and topically applied compounds in human skin using mass spectrometry. Issue 1 (December 2018) - Sjövall, Peter; Skedung, Lisa; Gregoire, Sébastien; Biganska, Olga; Clément, Franck; Luengo, Gustavo
Abstract The barrier functions of skin against water loss, microbial invasion and penetration of xenobiotics rely, in part, on the spatial distribution of the biomolecular constituents in the skin structure, particularly its horny layer (stratum corneum). However, all skin layers are important to describe normal and dysfunctional skin conditions, and to develop adapted therapies or skin care products. In this work, time-of-flight secondary ion mass spectrometry (ToF-SIMS) combined with scanning electron microscopy (SEM) was used to image the spatial distribution of a variety of molecular species, from stratum corneum down to dermis, in cross-section samples of human abdominal skin. The results demonstrate the expected localization of ceramide and saturated long-chain fatty acids in stratum corneum (SC) and cholesterol sulfate in the upper part of the viable epidermis. The localization of exogenous compounds is demonstrated by the detection and imaging of carvacrol (a constituent of oregano or thyme essential oil) and ceramide, after topical application ontoex vivo human skin. Carvacrol showed pronounced accumulation to triglyceride-containing structures in the deeper parts of dermis. In contrast, the exogenous ceramide was found to be localized in SC. Furthermore, the complementary character of this approach with classicalex vivo skin absorption analysis methods is demonstrated.